Relation between balance loss in floor exercises by male gymnasts and anthropometric features and balance - Manolya Akın; Oya Erkut Atılgan; Salih Pınar; Ufuk Alpkaya (Türk Spor ve Egzersiz Dergisi)
This study aims at looking into the relationship between losses of balance in floor exercises performed by male gymnasts at 17th International Bosporus Gymnastics Tournament and some of the anthropomorphic characteristics and the balance tests given under laboratory conditions. 15 male gymnasts volunteered for this research, (aged= 19.93 ± 2.98, training years12.87±3.68). In order to analyze the losses of balance in floor exercises, the floor routines were recorded by video, and each loss of balance following each gymnastic element was evaluated.  Also static – dynamic balance, body weight, height, arm span, leg and torso lengths were measured. Pearson Correlation coefficient was used for analyzing the relations between the data findings. It was found that there was no statistical relation between the losses of balance in floor exercises and static-dynamic balance test results (p gt;0.05). Also no correlation was found between floor exercise losses of balance and number of training years, height, body weight, arm span, torso length, and leg length (p gt;0.05). But it was observed that there was a negative correlation between dynamic balance test and body weight (r=-0.565 p lt;0.05) and between static balance with closed eyes and age (r=0.582 (p lt;0.05). A reasonable explanation for these results are that keeping one's balance after the element in artistic gymnastics is more likely to be a result of the technical mastery.